The unoccupied electronic structure characterization of hydrothermally grown ThO2 single crystals. Issue 3 (7th January 2014) - Kelly, T. D.; Petrosky, J. C.; Turner, D.; McClory, J. W.; Mann, J. M.; Kolis, J. W.; Zhang, Xin; Dowben, P. A.
Abstract Single crystals of thorium dioxide ThO2, grown by the hydrothermal growth technique, have been investigated by ultraviolet photoemission spectroscopy (UPS), inverse photoemission spectroscopy (IPES), and L3, M3, M4, and M5 X‐ray absorption near edge spectroscopy (XANES). The experimental band gap for large single crystals has been determined to be 6 eV to 7 eV, from UPS and IPES, in line with expectations. The combined UPS and IPES, place the Fermi level near the conduction band minimum, making these crystals n‐type, with extensive band tailing, suggesting an optical gap in the region of 4.8 eV for excitations from occupied to unoccupied edge states. Hybridization between the Th 6d/5f bands with O 2p is strongly implicated. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)